General public perceptions and motivations to adopt children from out-of-home care in New South Wales, Australia. (19th August 2019) - Luu, Betty; Wright, Amy Conley; Randle, Melanie
Abstract: Recent reforms in New South Wales (NSW), Australia, prioritise adoption over long-term foster care. While previous research has examined motivation to foster, less is known about the interest by the general public in adoption from out-of-home care. A general sample of the NSW public ( N = 1030) completed an online survey about adoption practices and their willingness to consider adopting from out-of-home care, with background questions on perceived social support and life satisfaction. Barriers to pursuing adoption were identified, including concerns about the characteristics of the child related to their experiences of care and personal impacts including financial costs. Availability of post-adoption supports was viewed positively as increasing interest in adoption. General Linear Model univariate analyses identified that likelihood of considering adoption was primarily predicted by younger age, knowing someone who had been adopted as a child, actively practicing religion, living in the city rather than a regional area and higher life satisfaction. Customised marketing campaigns can target people more likely to consider adoption, with messages that resonate with their social and psychological characteristics. There is also a need for policy changes to ensure adequate provision of post-adoption support.